Casing-material experiments with Pleurotus eryngii - Győrfi, J.; Hajdú, Cs. (International Journal of Horticultural Science, 2007)
Our research led to the gathering some relevant information about the growing technology of the Pleurotus eryngii. In some European countries this mushroom is quiet favourable. The detail of the growing technology has not been determined in detail yet. These partial results led us to carry on with the research towards a development of covering technology. With some new series of experiments and with the use of some new covering mixtures and their application of different thickness we are hoping to clarify the details of the technology.